1967
DOI: 10.1172/jci105505
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Heme on Heme Formation In Vivo: Possible Mechanism for the Regulation of Hemoglobin Synthesis*

Abstract: Summary. 1) The effect of hemin on heme synthesis was studied in vivo. Heme synthesis was measured by determining red cell 59Fe uptake and glycine-2-14C incorporation into red cell hemin in normal CF1 female mice.2) Both bovine and human hemin significantly decreased red cell 59Fe uptake 48, 72, and 96 hours after hemin injection.3) Glycine-2-14C incorporation into red cell hemin was decreased to 50% of control values after the administration of hemin (90 Jumoles per kg).4) There was no significant difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Assimilation of iron, formation of heme de novo, and protein synthesis in these cells are interrelated processes subject to control by the availability of endogenous heme. In whole animals and intact reticulocytes, hemin profoundly inhibits receptor-mediated iron uptake from plasma transferrin by an unknown mechanism (1,2). Under conditions of suboptimal or inhibited protein synthesis, rising concentrations of endogenous free heme probably account for the progressive decline in the rate of iron uptake by reticulocytes (2,3).…”
Section: Gm) Reduced Iron Transport But Increased Cell-associated Tramentioning
confidence: 99%
“…Assimilation of iron, formation of heme de novo, and protein synthesis in these cells are interrelated processes subject to control by the availability of endogenous heme. In whole animals and intact reticulocytes, hemin profoundly inhibits receptor-mediated iron uptake from plasma transferrin by an unknown mechanism (1,2). Under conditions of suboptimal or inhibited protein synthesis, rising concentrations of endogenous free heme probably account for the progressive decline in the rate of iron uptake by reticulocytes (2,3).…”
Section: Gm) Reduced Iron Transport But Increased Cell-associated Tramentioning
confidence: 99%
“…To our knowledge, this is the first report to demonstrate dissociation of heme moiety from the Hb molecule caused by an active metabolite of TNT. Early studies on heme biosynthesis in erythroid tissue have indicated that hemin itself inhibits the production of delta-aminolevulinic acid, a precursor for heme, both in vivo and in vitro (Karibian and London, 1965;Gallo, 1967). On the other hand, hemin induces heme oxygenase, the rate-limiting enzyme for heme degradation (Tenhunen et al, 1970).…”
Section: Fig 2 Effects Of Tnt and Its Metabolites On Hematotoxic Acmentioning
confidence: 99%
“…An inhibitory effect on erythropoiesis has with previous studies (Karibian & London been demonstrated in erythropoietin (ESF) 1965, Gallo 1967, Kilbridge et a1 1969 polycythaemic mice after injec -Ponka & Neuwirt 1969). However, some tions of intact red blood cells (RBC) or an authors have found a stimulatory effect on equal amount of haemolyzed cells (Linde-erythropoiesis with haemolysates, haeme mann 1974b).…”
mentioning
confidence: 89%